Schütz-Jahrbuch - Breig, Werner (Kassel Bärenreiter, 1979)
The Schütz-Jahrbuch has been published annually since 1979 as the central journal for contributions on Heinrich Schütz and his environment. The topics covered focus on music and musical culture of the 17th century and, within this framework, deal with baroque music in its entire range. The Schütz-Jahrbuch is the central publishing platform for the papers and lectures presented at the Heinrich Schütz Days and the International Heinrich Schütz Festivals.The yearbooks are made freely accessible with an embargo period of five years.
Keywords: Schütz, Heinrich -- 1585-1672; 17th Century (1601-1700); Music history; Cuckoo; Germany